EUROPEAN UNION INTEGRATION PROCESS: A LESSON LEARNED FOR ASEAN - Hutabarat, Leonard Felix (Indonesian Journal of International Law, 2016)
The paper first highlights the historical background of Indonesian foreign policy, the current “downto-earth and pro-people diplomacy”, as well as Indonesian foreign policy for the period of 2015-2019. Secondly, it will briefly describe the current and future global and regional situation that could become challenges and opportunities for Indonesia ahead. Third, it will also explain the current development of the European Union relations with Indonesia and ASEAN. Finally, the paper will conclude a lesson learned from European Union integration process for ASEAN.